2021
DOI: 10.1093/inthealth/ihab003
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision making for implementing e-health in light of the COVID-19 outbreak in Gulf Cooperation Council countries

Abstract: Background Electronic health (e-health) approaches such as telemedicine, mobile health, virtual healthcare and electronic health records are considered to be effective in increasing access to healthcare services, reducing operational costs and improving the quality of healthcare services during the coronavirus disease 2019 (COVID-19) outbreak, a pandemic resulting from the spread of a novel coronavirus discovered in December 2019. In this context, the aim of this study was to identify the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…3,7 The Gulf Cooperation Council (GCC) states, including Saudi Arabia, are in the process of digitalizing their healthcare infrastructure. 12,29 The current study showed that there is considerably low knowledge about telemedicine, with an average percentage of 63%. The knowledge of HCPs about telemedicine in their hospital, including telemedicine technology, medical applications, telemedicine tools, guidelines, and security and privacy policy, ranged between 55% and 72%.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…3,7 The Gulf Cooperation Council (GCC) states, including Saudi Arabia, are in the process of digitalizing their healthcare infrastructure. 12,29 The current study showed that there is considerably low knowledge about telemedicine, with an average percentage of 63%. The knowledge of HCPs about telemedicine in their hospital, including telemedicine technology, medical applications, telemedicine tools, guidelines, and security and privacy policy, ranged between 55% and 72%.…”
Section: Discussionmentioning
confidence: 61%
“…Prior to COVID-19, several studies discussed implementation of telemedicine and others post-pandemic. 5,12,15,20,[28][29][30] Kaliyadan et al (2020) showed mixed views of HCPs towards the use of telemedicine technology during the COVID-19 pandemic for diagnostic concordance and reliability. 5 HCPs across specialties debate the diagnostic concordance and suitability of telemedicine.…”
Section: Telemedicine and Privacymentioning
confidence: 99%
“…In addition, working parents with childcare responsibilities might find telemedicine more convenient than in-person visits because they can easily schedule online visits around their busy times. Similarly, telemedicine improves the efficiency of medical professionals like physicians, consultants, and nurses by allowing them to manage more remote patients within a limited time and cost [ 13 ]. Remarkably, the governments and medical service providers have taken telemedicine as an effective solution to crises led by catastrophes like COVID-19 [ 10 ], severe drought, and bushfires [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced digital technologies also improve national health systems by expanding the scope, transparency, and accessibility of online healthcare services and information, and by improving the provision of services to patients [ 4 , 13 ]. Telehealth plays an essential role in achieving strategic public health priorities because it reduces risk factors and health determinants by supporting intersectoral mechanisms, and it promotes the reduction in e-healthcare disparities and enhanced well-being [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, digital media is expanding the existing contact points and giving companies that offer this type of service better access to patients through telemedicine [ 18 ]. The significance of digital marketing is unquestionably connected to the modification and standardization of the marketing mix in accordance with the characteristics of target online patients for the services being offered [ 13 ]. To that end, several marketing mix options might be prioritized: e-healthcare services, promotional communication, and pricing [ 19 ].…”
Section: Introductionmentioning
confidence: 99%